Supportive or Confining? The Impact of War Metaphors From the COVID-19 Pandemic on Persons With Disabilities in Mainland China - Chen, Ren-Xing; Ge, Zhong-Ming; Hu, Shu-Ling; Tang, Wei-Zhong (Frontiers in Public Health, 2021)
Ensuring the well-being of persons with disabilities (PWDs) is a priority in the public sector during the coronavirus disease 2019 (COVID-19) pandemic. To contain this unprecedented public crisis in China, a set of nationwide anti-epidemic discourse systems centered on war metaphors has guided the epidemic's prevention and control. While the public is immersed in the joy brought by the stage victory, most ignore the situation of the disadvantaged PWDs. Accordingly, this study adopts and presents a qualitative research method to explore the impact of war metaphors on PWDs. The results showed that while there was some formal and informal support for PWDs during this period, they were increasingly marginalized. Owing to the lack of a disability lens and institutional exclusion, PWDs were placed on the margins of the epidemic prevention and control system like outsiders. Affected by pragmatism under war metaphors, PWDs are regarded as non-contributory or inefficient persons; therefore, they are not prioritized and are thus placed into a state of being voiceless and invisible. This research can provide inspiration for improving public services for PWDs in the context of COVID-19.